Glutathione and nitrite in induced sputum from patients with stable and acute asthma compared with controls - Deveci, F; Ilhan, N; Turgut, T; Akpolat, N; Kirkil, G; Muz, MH (Elsevier Science Inc, 2004)
Background: Oxidative stress is believed to play an important role in the pathogenesis of asthma. Determining the reduced glutathione (GSH) and nitric oxide (NO) contents of the airway is useful when investigating oxidative stress in the lung. Objective: To explore antioxidant defenses by measuring sputum GSH levels and to evaluate oxidant stress by measuring sputum nitrite (NO2-) levels in asthma patients. Methods: Sputum GSH, NO2- cell counts, and plasma NO2- contents were evaluated in 11 patients with stable asthma, 10 patients with acute asthma attacks, and 11 controls. Results: The highest GSH content in sputum samples was in stable asthma patients compared with the other groups (P <.001), and patients with exacerbations of asthma had a greater GSH content than controls (P <.001). Mean sputum NO2- content was significantly lower in controls than in acute (P =.001) and stable (P < .001) asthma patients. There was no significant difference in sputum NO2- contents between acute and stable asthma patients, although there was a trend toward higher levels in acute asthma patients (P =.38). Conclusions: Sputum induction can be used to obtain bronchial secretions for the evaluation of GSH and NO2- contents. Oxidative stress is chronic and probably less severe in patients with stable asthma. Glutathione and NO2- may serve as markers for determining the extent of the oxidative processes in asthma, which is characterized by chronic airway inflammation.
Keywords: Oxygen Free-Radicals; Airway Inflammation; in-Vivo; Lipid-Peroxidation; Oxide Synthase; Mild Asthma; Fluid; Lung; Epithelium; Generation